Subgroup analysis of virological response rates with once‐ and twice‐daily darunavir/ritonavir in treatment‐experienced patients without darunavir resistance‐associated mutations in the ODIN trial. Issue 7 (10th March 2013) - Sension, M; Cahn, P; Domingo, P; Hodder, S; Opsomer, M; Lathouwers, E; Van de Casteele, T; Tomaka, F
<x xml:space="preserve">Abstract</x> Background ODIN (once‐daily darunavir in treatment‐experienced patients) was a 48‐week, phase III, randomized, open‐label trial comparing once‐daily (qd) darunavir/ritonavir (DRV/r) 800/100 mg with twice‐daily (bid) DRV/r 600/100 mg, both with an optimized background regimen [OBR; at least two nucleoside reverse transcriptase inhibitors (NRTIs)], in treatment‐experienced, HIV‐1‐infected adults with no DRV resistance‐associated mutations (RAMs) at screening. Week 48 analyses of virological response by subgroups are reported. Methods A total of 590 patients were randomized to receive qd (n = 294) or bid (n = 296) DRV/r. Virological response (HIV‐1 RNA < 50 copies/mL) was assessed according to: screening HIV‐1 RNA (≥ or < 50 000 copies/mL), CD4 cell count, prior protease inhibitor (PI) use, number of active NRTIs in the OBR, presence of mutations (primary PI mutations, PI RAMs or M184V/I), gender, age, race, HIV‐1 clade and adherence. Results Baseline characteristics were well balanced between arms and across subgroups. Response rates were comparable between qd and bid DRV/r treatments for all subgroups examined. Response rates were 78.4 and 76.8% in the qd and bid treatment arms, respectively, in patients with baseline HIV‐1 RNA ≤ 50 000 copies/mL and 52.8% in both arms in those with > 50 000 copies/mL. Response rates for the qd and bid treatment arms by baseline CD4 cell count were also similar (69.6 vs. 65.2% for <200 cells/μL; 72.2 vs. 74.8% for 200− < 350 cells/μL; 77.0 vs. 74.3% for ≥ 350 cells/μL). Conclusions DRV/r administered either qd or bid provided effective treatment for antiretroviral treatment‐experienced patients with no DRV RAMs, with comparable response rates across all subgroups studied. Low patient numbers in specific subgroups may limit interpretation of these specific subgroup results.